A remark on non-local theories of elasticity, piezoelectric materials etc. (December 2015) - Atkinson, Colin
Abstract: A reminder is made of difficulties with applications of non local theories (which represent stress as a weighted integral of strain) to generating finite stresses at line crack tips.